PERAN KOMUNIKASI PERSUASIF GURU DALAM MERUBAH PERILAKU UNTUK BERSEDIA DI VAKSIN COVID-19 SISWA SMA NEGERI 01 SUNGAI APIT KABUPATEN SIAK - Hardani '; Hevi Susanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
In the era of technological change occurring in the world of education, face-to-face learning carried out in schools suddenly underwent a very drastic change to become online learning. Sungai Apit 01 Public High School will start carrying out face-to-face activities again in February 2021, the start of face-to-face activities requires school students to carry out 3M and take part in the covid-19 vaccination, so there is a need for a role with persuasive communication carried out in order to maximize the program being held . So this study aims to see the credibility of persuaders, the form of messages, the media used by SMA Negeri 01 Sungai Apit and the effect of persuasive teacher communication in providing information and education. This study used a descriptive qualitative research method with a purposive technique in which the informants consisted of school principals, members of the Covid-19 team, homeroom teachers, teachers, students of SMA Negeri 01 Sungai Apit and parents/guardians of SMA Negeri 01 Sungai Apit. Collecting data using unstructured interview techniques, non-participant observation and documentation. The data analysis technique used Miles and Huberman's interactive data model by validating the data using extended participation and triangulation techniques. The results showed that the teachers of SMA Negeri 01 Sungai Apit had the credibility of the persuader, namely, first, the expertise in which the persuader was an education expert, and had gained knowledge about the co-19 vaccination. Second, it can be trusted, where the persuader in conveying the message refers to the health rules and has already carried out the vaccination. The form of the message produced is in the form of a verbal message which includes elements of clarity, straightforwardness and accuracy, as well as nonverbal which shows a style of language that is impressively simple so that it is easy for you to understand and accept. With the media used several media, namely social media in the form of Facebook, Instagram and websites. Outdoor media in the form of billboards and banners. As well as the effects received by students, namely cognition: students observe, see, pay attention to the school in providing information and education. affective: the feeling that students want to take part and be interested in the co-19 vaccination program. conation: students see posters and banners and are moved to vaccinate, there is no coercion from the teacher and the school, learn to receive vaccinations. Keywords: The Role of Communication, Teacher, SMA Negeri 01, Siak Regency